FGD Strategi Penyediaan Pakan Berbasis Teknologi Pengolahan Limbah untuk Meningkatkan Produktivitas Ternak Kambing di Berkah Mandiri Farm Desa Pejambon Kecamatan Negeri Katon Kabupaten Pesawaran - Melia Afnida Santi; Kunaifi Wicaksana; Rikardo Silaban; Andre Meiditama Kasenta (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2024)
The devotion aims to increase the capability of the farmers at Berkah Mandiri Farm regarding feed supply technology by optimizing the availability of agro-industrial waste by products. The livestock business managed by the group focuses on small ruminant commodities that is Goats and Sheep. Community service are carried out through an approach method (Consuling) and active discussion (Forum Group Discussion) with the head of the livestock business manager. Informations were obtained in the devotion is also descriptively analyzed by utilizing various secondary data obtained at service locations. The location for the activity is Pejambon Village, Negeri Katon District, Pesawaran Regency. The results of FGD show that the level of knowledge for breeders is relatively high in livestock rearing management and relatively low in terms of feed science and technology, especially through the use of agro-industrial waste. Based on the activities carried out, it can be concluded that Berkah Mandiri Farm really needs assistance efforts in the field related to various waste processing science and technology in order to increase the availability of alternative feed sources and increase the productivity of small ruminant livestock.